Anti-Fat Attitudes Towards Weight Gain Caused by the COVID-19 Pandemic or by “Unhealthy” Lifestyle Choices - Daniel Regan; Mackenzie Bjornerud; Mark J. Kiss; Melanie A. Morrison; Todd G. Morrison (Obesities)
Given the ubiquity of anti-fat prejudice, in this experimental study, we tested whether weight gain attributed to COVID-19 would influence evaluations of overweight male and female targets. Female participants (N = 160) were randomly assigned to read one of four mock medical forms that outlined distractor medical information (e.g., blood requisition results), the sex of the target (male vs. female) and stated reason for weight gain (unhealthy lifestyle choices vs. inactivity due to the COVID-19 lockdown). Participants evaluated the patient on a series of binary adjectives (e.g., lazy/industrious), and completed measures assessing anti-fat attitudes (i.e., fear of becoming fat and belief in the controllability of weight), internalization of ideal standards of appearance, and BMI (i.e., self-reported weight and height). Contrary to our predictions, we found that overweight male and female patients were evaluated similarly regardless of whether their weight gain was attributable to unhealthy lifestyle choices or inactivity due to the COVID-19 pandemic. Finally, believing that one’s weight is controllable and internalizing general standards of attractiveness correlated positively with fat disparagement of the medical patients. Participants’ BMI and fear of fat, however, were negligibly related to fat disparagement. Possible explanations for our findings, implications for healthcare settings, and directions for future research are explored.